Predetermined Performance Control of Spacecraft Formation Based on SE(3) Error Description - Lijun Li; Yuanda Wang; Qin Yang; Erhan Wang (International Journal of Aerospace Engineering, 2025)
For the obstacle avoidance and formation maintenance issues of spacecraft formation, a control method with prescribed performance is proposed. Firstly, an error description system based on SE (3) is established. Secondly, to simplify the control system, collision avoidance, formation control of leading spacecraft, and containment control of following spacecraft are combined. Finally, the control errors are kept within the prescribed performance function range using prescribed performance control. Simulation results of spacecraft formation completing complex tasks under external disturbances validate the effectiveness of the proposed control scheme.